2014
DOI: 10.1111/joa.12178
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of hepatic arteriolo‐portal venular shunts evaluated by 3D micro‐CT imaging

Abstract: The liver differs from other organs in that two vascular systems deliver its blood -the hepatic artery and the portal vein. However, how the two systems interact is not fully understood. We therefore studied the microvascular geometry of rat liver hepatic artery and portal vein injected with the contrast polymer Microfil â .Intact isolated rat livers were imaged by micro-CT and anatomic evidence for hepatic arteriolo-portal venular shunts occurring between hepatic artery and portal vein branches was found. Sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…; Van Steenkiste, ; Debbaut, ; Kline et al. ). In addition, cirrhosis is considered the principal cause of intrahepatic portosystemic shunts (Lutz et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Van Steenkiste, ; Debbaut, ; Kline et al. ). In addition, cirrhosis is considered the principal cause of intrahepatic portosystemic shunts (Lutz et al.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, new vessels may originate to support the blood supply and venous drainage of the regenerative nodules. The resulting neovasculature is primarily located in the fibrotic regions and bypasses functional liver tissue, thereby aggravating the liver insufficiency (Hano & Takasaki, 2003;Vanheule et al 2008;Van Steenkiste, 2010;Debbaut, 2013;Kline et al 2014). In addition, cirrhosis is considered the principal cause of intrahepatic portosystemic shunts (Lutz et al 2004), although the majority of portosystemic shunts observed in PHT are extrahepatic.…”
Section: Introductionmentioning
confidence: 99%
“…Histomorphometric analyses are used to describe angiogenesis, but are limited in the ability to identify the three‐dimensional (3D) interconnectivity of the vasculature in serial histological sections (Kline et al, ; Perrien et al, ) and focuses on representing superficial blood flow (Zagorchev et al, ). Connectivity defines the maximal number of branches that may be cut without separating the structure (Zagorchev et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…As technology continues evolving, modern micro‐CT systems are more commonly available and are capable of generating very small voxels with short scan acquisition times allowing both ex vivo and in vivo scanning (Zagorchev et al, ). Moreover, due to voxels as small as 1 μm, the vascular system in rat and even mice could now be visualized (Deshpande et al, ; Kline et al, ; Lee, Barbe, Scalia, & Goldfinger, ; Perrien et al, ). As perfusion with a radiopaque contrast agent is the only requirement to delineate the vascular tree, a close‐meshed network of smaller vessels, contrast enhanced micro‐CT can become a powerful tool in quantifying angiogenesis (Perrien et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…There is continued interest for its various procedures and chemotherapeutic agents used despite potential risks and complications [6]. After the successful occlusion of the arterial blood flow of the malignant nodule, the portal blood regurgitation into the adjacent sinusoid vessels may favor tumor remnants, thus reducing the efficacy of TACE [7,8].…”
Section: Introductionmentioning
confidence: 99%